Odpowiedź :
[tex]a)(3 \sqrt{50} + 2 \sqrt{8} - \sqrt{32} ) \div \sqrt{2} =(3 \sqrt{25 \times 2} + 2 \sqrt{4 \times 2} - \sqrt{16 \times 2} ) \div \sqrt{2} = (15 \sqrt{2} + 4 \sqrt{2} - 4 \sqrt{2} ) \div \sqrt{2} = 15 \sqrt{2} \div \sqrt{2} = 15[/tex]
[tex]b)(6 \sqrt{24} - 2 \sqrt{54} + \sqrt{96} ) \div \sqrt{3} = (6 \sqrt{4 \times 6} - 2 \sqrt{6 \times 9} + \sqrt{16 \times 6} ) \div \sqrt{3} = (12 \sqrt{6} - 6 \sqrt{6} + 4 \sqrt{6} ) \div \sqrt{3} = 10 \sqrt{6} \div \sqrt{3} = 10 \sqrt{2} [/tex]
[tex]c)(8 \sqrt[3]{ - 16} + 2 \sqrt[3]{ - 54} - 3 \sqrt[3]{ - 128} ) \div \sqrt[3]{2} = ( - 16 \sqrt[3]{2} - 6 \sqrt[3]{2} + 12 \sqrt[3]{2} ) \div \sqrt[3]{2} = 10 \sqrt[3]{2} \div \sqrt[3]{2} = 10[/tex]
[tex]d)(4 \sqrt[3]{625} - 3 \sqrt[3]{40} + \sqrt[3]{320} ) \div \sqrt[3]{5} = (20 \sqrt[3]{5} - 6 \sqrt[3]{5} + 4 \sqrt[3]{5} ) \div \sqrt[3]{5} = 18 \sqrt[3]{5} \div \sqrt[3]{5} = 18[/tex]